2012
DOI: 10.1111/j.1365-2788.2012.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of leisure participation of youth and adults with developmental disabilities

Abstract: The findings reveal interesting patterns of participation in leisure activities from the viewpoint of youngsters and adults with developmental disabilities. Leisure participation among people with developmental disabilities is likely to be more affected by environmental factors than by personal factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 31 publications
3
86
1
6
Order By: Relevance
“…It is expected of MS patients as well as other people to spend most of their lives with others. Going to a party, represents the most common event of social life, which has also been mentioned in several studies [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected of MS patients as well as other people to spend most of their lives with others. Going to a party, represents the most common event of social life, which has also been mentioned in several studies [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…This causes the production of heat within their bodies and may result in inflicting further damage to patients' condition. Many other researchers have pointed out physical factors in their studies [23,27,28,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In a small study (n = 4), it was found that participants mostly engaged in sedentary, passive activities, including spending 23% of their time "doing nothing" (Sparrow & Sharp, 1991). In a Spanish study with 237 adults with ID, the most common recreational activities at home were watching TV, resting, and listening to music with low levels of participation in physical activities (Badia, Orgaz, Verdugo, & Ullán, 2013).…”
Section: Diagnostic and Statistical Manual Of Mentalmentioning
confidence: 99%
“…These elements are multifactorial and form a whole to be considered when addressing the inclusion of people with disabilities in leisure. According to Longo, Badia and Orgaz (2013), personal and environmental factors may have a greater impact on youth participation than only the family environment. This can be explained by the fact that the disability is a result of interrelations between the person and their environment (societal, social environment).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Finally personal factors should be considered, such as age, gender, motor and social skills as well as motivation. The following section aims to identify knowledge relating to both the school and the role of physical educators through a review of the literature.Unauthenticated Download Date | 5/13/18 6:24 AM Determinants of participation in adapted recreational and competitive physical activity 138 School, physical activity, and students with disabilities Although policies and regulations affect participation in recreational and competitive physical activity (Badia & al., 2013;Shikako-Thomas et al, 2008), equipment and infrastructures play a significant role (King et al, 2006). In addition, schools play an essential role in acquiring a healthy lifestyle.…”
mentioning
confidence: 99%